Malaysian instructional television - Fatimah, Binti Ali 1945-
This study is the first attempt towards an understanding of the Instructional Television in Malaysia. The Critical-Descriptive-Survey method of reseacrh was employed. The data used were gathered from circulars, documents, periodicals, and results of informal interviews. The main findings include the formation of the Malaysian Instructional Television, its organization and administration, its production, and its utilization. For effective utilization, it was suggested that more efforts should be taken towards making headmasters and teachers gain deeper understanding of the role of Instructional Television and that closer and more effective supervision be made.